Research on the material flow and joining performance of two-strokes flattening clinched joint. (December 2021) - Peng, Hao; Chen, Chao; Ren, Xiaoqiang; Ran, Xiangkun; Gao, Xiaolei
Abstract: Clinching technology is widely used on thin-walled structures, but the joining of some special functional surfaces that require high strength is ignored by researchers. In the present work, a new joining technology suitable for functional surfaces, especially flat surfaces, called two-strokes flattening clinching (TFC), was introduced, which performs high-strength connections with a flat sheet surface. AA5052 sheets with thickness of 2.0 mm were adopted for experimental study of TFC process. The bottom dies are composed of the bottom ring, flap gaskets and anvil. AA5052 sheets are extruded by the punch into the bottom dies to form the initial clinched joint in the first stroke. The initial clinched joint is reverse stamped by different forces to form the TFC joint in the second stroke. The tension-shearing and cross-tension experiments were conducted to evaluate the mechanical performance of TFC joints. The material flow, static strength and energy absorption were investigated in this work. Furthermore, the relationship between neck thickness and interlock of the TFC joints under different flattening forces was studied. The result showed that the TFC joints have good mechanical performance. The tension-shearing and cross-tension strength reached 2951 N and 1646 N, respectively. The protrusion of joint disappears completely at a force of 35 kN, which means that the TFC process is able to join some functional surfaces and ensure good mechanical performance. Highlights: A two-strokes flattening clinching process was proposed and introduced. The neck thickness and interlock increase with the increasing opposing force. Two-strokes flattening clinching increase the strength of joint. Two-strokes flattening clinching ensure good mechanical properties of joint.